«Неолітична революція» в Європі. Проблема походження індоєвропейців - Сегеда, С. (Народна творчість та етнографія, 2008)
The author of this article examines the peculiarities of the final stage of the late Stone Age and accents attention on the problem of the Indo-European’s origin.